Métodos de apreensão paisagística aplicados em sítios históricos das Missões Jesuítico-Guaranis: contribuição a trabalhos de campo em Geografia - Yuri Potrich Zanatta; Reginaldo José de Souza; Éverton de Moraes Kozenieski (Terr@ Plural)
This paper aims to evaluate the “Urban Landscape Catalog” and “Topoceptive Site Assessment” methods as resources for landscape apprehensions of the tourist sites São Miguel Arcanjo (Brazil), San Ignácio Miní (Argentina) and Santísima Trinidad del Paraná (Paraguay). The article is structured by presenting the fundamentals that guide the chosen methods, characterization of the tourist sites under investigation and results from the application of the methods. Finally, readers are presented with an evaluation of the methods chosen as potential resources for the seizure of heritage objects and landscape elements that are presented to visitors/tourists. It is concluded that the methods, whose results are based on the observers’ vision, are strategies that present new elements to landscape studies classically present in Geography.